PERAN MEDIA AUDIO-VISUAL DALAM PEMBELAJARAN TEMATIK KELAS V SDN 06 PINOH UTARA - MARDIANA MARDIANA; Novi Harumiati; Linda Dwi Saputri (Bestari: Jurnal Pendidikan dan Kebudayaan, 2023)
Abstract : This study aims to find out how the role of audio-visual media in thematic learning for class V SDN 06 Pinoh Utara. Advances in technology that continue to develop from year to year provide many benefits, including in the world of education, namely helping to meet needs and expedite the learning process such as being able to obtain material from the internet, learn to use media, applications and provide other benefits.This study uses qualitative research methods, qualitative approaches, and descriptive qualitative research types. Research data were obtained by conducting observations, interviews, and documentation studies on research subjects. There were two subjects in this study, the main subject of class V students and the supporting subject of two class teachers.The results obtained after applying audio-visual media in class V thematic learning audio-visual media can help develop students' thinking skills, develop students' imaginations, and attract students' attention. The thinking ability of students is evidenced by an increase in students' understanding of learning by thinking logically. develop the imagination of students, as evidenced by research data which shows that there are students who are able to develop ideas after learning material is presented in the form of learning videos. attract the attention of participants, evidenced when learning uses audio-visual media in the form of learning videos which show the attitude of students to pay more attention to the teacher, to be calm and orderly, the willingness of students to answer questions, ask questions, do assignments/quizzes given increases, students become more active in class, and able to conclude learningKeywords: the role of learning media, audio-visual media, thematic learningAbstrak: Penelitian ini bertujuan untuk mengetahui bagaimana peran media audio-visual dalam pembelajaran tematik kelas V SDN 06 Pinoh Utara. Kemajuan  teknologi yang terus berkembang dari tahun ketahun memberikan banyak manfaat termasuk dalam dunia Pendidikan yaitu membantu memenuhi kebutuhan dan memperlancar proses pembelajaran seperti dapat memperoleh materi dari internet, belajar menggunakan media, aplikasi dan memberikan  manfaat lainnya. Penelitian ini menggunakan metode penelitian kualitatif, pendekatan kualitatif, dan jenis penelitian kualitatif deskriptif. Data pnelitian diperoleh dengan melakukan observasi, wawancara, dan studi dokumentasi terhadap subjek penelitian. Subjek dalam penelitian ini ada dua, subjek utama peserta didik kelas V dan subjek pendukung dua orang guru kelas. Hasil yang diperoleh setelah menerapkan media audio-visual dalam pembelajaran tematik kelas V media audio-visual dapat membantu mengembangkan kemampuan berpikir peserta didik, mengembangkan imajinasi peserta didik, dan menarik perhatian peserta didik. Kemampuan berpikir peserta didik, dibuktikan dengan adanya peningkatan peserta didik dalam memahami pembelajaran dengan berpikir secara logis. Mengembangkan imajinasi peserta didik, dibuktikan dengan data hasil penelitian yang menunjukan adanya peserta didik yang mampu mengembangkan ide-ide yang setelah materi pembelajaran disajikan dalam bentuk video pembelajran. Menarik perhatian peserta, dibuktikan saat pembelajaran menggunakan media audio-visual berupa video pembelajaran yang menunjukan sikap peserta didik menjadi lebih memperhatikan guru, bersikap tenang dan teratur, kemauan peserta didik untuk menjawab pertanyaan, bertanya, mengerjakan tugas/kuis yang diberikan meningkatkan, peserta didik menjadi lebih aktif di kelas, dan mampu menyimpulkan pembelajaran.Kata Kunci : peran media pembelajaran, media audio-visual, pembelajaran tematik